2016
DOI: 10.1016/j.nima.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Fano factor in inorganic scintillators

Abstract: The Fano factor of an integer-valued random variable is defined as the ratio of its variance to its mean. Correlation between the outputs of two photomultiplier tubes on opposite faces of a scintillation crystal was used to estimate the Fano factor of photoelectrons and scintillation photons. Correlations between the integrals of the detector outputs were used to estimate the photoelectron and photon Fano factor for YAP:Ce, SrI2:Eu and CsI:Na scintillator crystals. At 662 keV, SrI2:Eu was found to be sub-Poiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In their experiments, they received for the photoelectrons and photons Fano factors F n = 0.72 ± 0.06 and F N = 0.10 ± 0.16 for the scintillator LaBr 3 :Ce with photomultipliers Hamamatsu R6233‐100 and F n = 0.68 ± 0.07 and F N = 0.09 ± 0.20 for photomultipliers Hamamatsu R7600U‐200 and confirmed these results in their following article …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In their experiments, they received for the photoelectrons and photons Fano factors F n = 0.72 ± 0.06 and F N = 0.10 ± 0.16 for the scintillator LaBr 3 :Ce with photomultipliers Hamamatsu R6233‐100 and F n = 0.68 ± 0.07 and F N = 0.09 ± 0.20 for photomultipliers Hamamatsu R7600U‐200 and confirmed these results in their following article …”
Section: Introductionsupporting
confidence: 59%
“…Whether the experimental results are the evidence of sub‐Poissonian photon statistics in scintillators? Not at all!…”
Section: Interrelation Between Photoelectron and Photon Statistics Inmentioning
confidence: 99%
“…When the value of F < 1, it is in the sub-Poissonian case, whereas when F > 1, it is in the super-Poissonian case. Smaller values of F imply smaller variance and less noise [55]. It is very well known that a lower value of F implies better energy resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Swank showed how stochastic variation in a scintillator's gain reduces DQE(0) by a scalar:As=m12m0m2,where m i represents the i ‐th moment of the scintillator's pulse height spectrum. Random gain fluctuations are caused not only by depth dependence in light escaping the scintillator, but also by variations in the energy deposited within the scintillator per absorbed x ray, energy‐dependence in its x ray conversion efficiency (i.e., nonproportionality), and intrinsic variability in its scintillation processes (i.e., Fano noise) …”
Section: Introductionmentioning
confidence: 99%
“…Random gain fluctuations are caused not only by depth dependence in light escaping the scintillator, but also by variations in the energy deposited within the scintillator per absorbed x ray, energy-dependence in its x ray conversion efficiency (i.e., nonproportionality), 13 and intrinsic variability in its scintillation processes (i.e., Fano noise). 14 Lubberts showed that depth dependence in a scintillator's spatial blur, that is, MTF(z,f), causes the square of its MTF to decrease more rapidly than its NNPS with increasing spatial frequency. This effect causes a "roll-off" in the DQE of energy-integrating detectors, and is known as the "Lubberts effect".…”
Section: Introductionmentioning
confidence: 99%